Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s10461-007-9277-9
|View full text |Cite
|
Sign up to set email alerts
|

HIV, Homelessness, and Public Health: Critical Issues and a Call for Increased Action

Abstract: Homelessness and housing instability are significant public health issues that increase the risks of HIV acquisition and transmission and adversely affect the health of people living with HIV. This article highlights the contributions of selected papers in this special issue of AIDS and Behavior and considers them within the broader context of prior research on the associations between housing status and HIV risk, use of HIV medical care, adherence to HIV treatment, and the physical health of HIV-seropositive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 46 publications
2
63
0
Order By: Relevance
“…In other words, living on the streets and insecurity related to having no housing 7,11,20,28 are per se factors that bring about situations of greater exposure to HIV such as violence and no access to services. 14,26,29 These same particularities may largely explain the study fi nding that young, female and homeless individuals engaging in homosexual sex are more vulnerable to HIV infection. We found that, among those engaging in homosexual sex, at least one out of 10 are living with HIV.…”
Section: Discussionmentioning
confidence: 96%
“…In other words, living on the streets and insecurity related to having no housing 7,11,20,28 are per se factors that bring about situations of greater exposure to HIV such as violence and no access to services. 14,26,29 These same particularities may largely explain the study fi nding that young, female and homeless individuals engaging in homosexual sex are more vulnerable to HIV infection. We found that, among those engaging in homosexual sex, at least one out of 10 are living with HIV.…”
Section: Discussionmentioning
confidence: 96%
“…28 A number of studies have shown that people who lack stable housing are more likely than those with stable housing to delay HIV treatment and less likely to receive optimal antiretroviral therapy. [29][30][31][32] One large study found that homeless HIV-infected participants had lower CD4 cell counts (cells that are part of the human immune system) than their stably housed counterparts and were less likely to report having an undetectable viral load; both of these are indicators of more advanced HIV disease. 31 Stable housing increases the ability of HIV-infected people receiving treatment to consistently adhere to their antiretroviral drug regimens, which in turn improves their health, minimizes their hospital visits-and the associated costsand decreases their mortality.…”
Section: Stable Housingmentioning
confidence: 99%
“…Sleepiness can also be secondary to HIV itself or comorbid conditions. A distorted sleep pattern is also common in those who are homeless where it may lead them to patients sleeping through medication time (Laws et al, 2000;Wolitski et al, 2007).…”
Section: Forgetfulness and Oversleepingmentioning
confidence: 99%
“…Homelessness and inadequate housing make it more difficult for people to manage and live with HIV/AIDS. Homelessness contributes to non-adherence to HAART (Wolitski et al, 2007) and is associated with several risk factors for non-adherence. High levels of social isolation and low levels of social support are seen in homeless Aboriginal people (Reading, 2010).…”
Section: Housingmentioning
confidence: 99%
See 1 more Smart Citation